2015
DOI: 10.21121/eab.2015118006
|View full text |Cite
|
Sign up to set email alerts
|

Eğitim ve Gelir

Abstract: Education, which enhances human capital's qualification and productivity and increases individual's future earnings, is also one of the most effective political instruments that permanently solves income inequalities problem. In this study, utilizing Quantile regression techniques in Denizli we analyzed the effect of education level of mother and father on household's income. Results indicated that while the impact of mother's educational level on income does not show a significant difference for different poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
(26 reference statements)
1
2
0
2
Order By: Relevance
“…On the other hand, the effect of master's or doctoral degrees are the highest for women in q90. This result supports the studies of Çiftçi and Kangallı (2015) investigating the contribution of parents' education status living in Denizli to family income for 2012. In their study, similar to our results, they found that increases in the education of fathers from the lowerincome group (q10) to the median income group (q90) increased the family income more, but in the high-income groups, the increases in the education of the mothers increased the family income more.…”
Section: Estimation Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, the effect of master's or doctoral degrees are the highest for women in q90. This result supports the studies of Çiftçi and Kangallı (2015) investigating the contribution of parents' education status living in Denizli to family income for 2012. In their study, similar to our results, they found that increases in the education of fathers from the lowerincome group (q10) to the median income group (q90) increased the family income more, but in the high-income groups, the increases in the education of the mothers increased the family income more.…”
Section: Estimation Resultssupporting
confidence: 88%
“…Despite the significant increase in the number of educated individuals, wage incomes changed in favor of educated individuals between the years 2004-2010. Çiftçi and Kangallı (2015) examine the effects of increases in parents' education levels on family income in Denizli province in 2012. They use least squares and quantile regression methods in their studies.…”
Section: Literaturementioning
confidence: 99%
“…This is thought to be incidental since the level of education effects the type of house and the area (rural/urban) lived in. 43,44 Although the economic status of students' families also affects the house and the area lived in it was not found to be statistically significant (p=0.053). Which might be caused by the importance of agriculture in the economy of Anatolia region.…”
Section: Dovepressmentioning
confidence: 91%
“…254-256). 2006Kadın Erkek Eşitliği İçin Yol Haritası, 2010Avrupa 2020Stratejisi: Akıllı, Sürdürülebilir ve Kapsayıcı Büyüme İçin Avrupa Stratejisi, 2010Kadınlar Şartı, 2010-2015Kadın-Erkek Eşitliği İçin Strateji, 2016-2019 Toplumsal Cinsiyet Eşitliği Stratejik Taahhütleri kapsamında; kadın istihdamının arttırılması, iş ve aile yaşamının uyumlaştırılması, eşit ve eş değerde işe eşit ücret, kadın girişimciliğin desteklenmesi ve kadın yoksulluğu ile mücadele, karar alma süreçlerinde eşitliği yakalama, toplumsal cinsiyet temelli şiddete son verilmesi, esnek çalışma düzenlemelerinin yapılması, çocuk ve yaşlı bakımının desteklenmesine yönelik önlemlerin alınması gerekliliğine dikkat çekilmiştir (Yılmaz, 2017: 202-204;Ceylan-Ataman, 2017).…”
Section: Ab Ve Türkiye'de Cinsiyete Dayalı üCret Eşitsizliği Kapsamında Yasal Düzenlemelerunclassified